Family health sheets: a vital instrument for village health workers providing comprehensive healthcare - Faraz Alizadeh; Aravind Addepalli; Shombit R. Chaudhuri; Annie Modesta Budongo; Immaculate Owembabazi; Gloria Fung Chaw; Sam Musominali; Gerald Paccione (BMC Health Services Research, 2021)
Abstract Introduction Community Health Worker (CHW) programs have long been used to provide acute care for children and women in healthcare shortage areas, but their provision of comprehensive longitudinal care for chronic problems is rare. The Village Health Worker (VHW) program, initiated in 2007, is an example of a long standing “horizontal” CHW program in rural Southwestern Uganda that has delivered village-level care for chronic disease based on a biannual village health census that identifies individual and family health risks. To facilitate continuity of care for problems identified, health census data were electronically transformed into family-specific Family Health Sheets (FHS) in 2016 which summarize the pertinent demographic and health data for each family, as well as health topics the family would like to learn more about. The FHS, evaluated and discussed here, serves as an epidemiologically-informed “bedside” tool to help VHWs provide longitudinal care in their villages. Methods 48 VHWs in the program completed a survey on the utility of the FHS and 24 VHWs participated in small discussion groups. Responses were analyzed using both quantitative and standard conceptual content analysis models Results 46 out of 48 VHWs reported that the FHS made them a “much better VHW.” In addition to helping target interventions in child health, women’s health, and sanitation, the FHS assisted follow-up of non-communicable diseases in the community. In discussion groups, VHWs reported that the FHS helped them understand risks for future disease, facilitated earning stipends, and increased credibility and trust in the community. Limitations cited were the infrequent updates of the FHS, only biannually with the census, and the lack of cross-reference capability by health problem. Discussion The FHS supports VHWs in providing longitudinal and comprehensive healthcare of chronic diseases in their villages. Limitations, potential solutions, and future directions are discussed.